2017
DOI: 10.1002/hbm.23547
|View full text |Cite
|
Sign up to set email alerts
|

In vivo detection of lateral–ventral tier nigral degeneration in Parkinson's disease

Abstract: Objective To use a novel region of interest to measure neuromelanin-sensitive MRI contrast changes in the lateral-ventral tier of substantia nigra pars compacta in Parkinson’s disease (PD). Background Histopathological studies of PD have demonstrated both massive loss of melanized dopamine neurons and iron accumulation in the substantia nigra pars compacta. Neurodegeneration is most profound in the lateral-ventral tier of this structure. We have previously shown in both healthy controls and individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
45
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 33 publications
17
45
2
1
Order By: Relevance
“…Similar findings have been reported in previous studies using 2D NSMRI [18,20]. Recent studies by Huddleston et al [27] and Langley et al [28] have utilized in vivo detection of the lateral-ventral tier of the SNc and demonstrated the selective vulnerability of this nigral sub-region in PD. In our study, the CRs of the lateral SNc were found to correlate with the disease duration of PD.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar findings have been reported in previous studies using 2D NSMRI [18,20]. Recent studies by Huddleston et al [27] and Langley et al [28] have utilized in vivo detection of the lateral-ventral tier of the SNc and demonstrated the selective vulnerability of this nigral sub-region in PD. In our study, the CRs of the lateral SNc were found to correlate with the disease duration of PD.…”
Section: Discussionsupporting
confidence: 85%
“…Recent studies by Huddleston et al . and Langley et al . have utilized in vivo detection of the lateral–ventral tier of the SNc and demonstrated the selective vulnerability of this nigral sub‐region in PD.…”
Section: Discussionmentioning
confidence: 90%
“…33 Another recent study suggested that the in vivo assessment of neuromelanin with magnetization transfer contrast, particularly in the pSN pars compacta, might be a promising biomarker of the disease. 34 Similar to the ventral SN, PD pathology studies have also shown the pSN to be involved early and to a greater extent when compared with the aSN. 2 Using calbindin D 28K immunostaining techniques, it was demonstrated that the greatest cell loss was found in the so-called nigrosome 1 region of the SN.…”
Section: Discussionmentioning
confidence: 99%
“…Previous SN imaging studies in PD have also found larger effects to be localized to the pSN, as reported in several different modalities including DTI, neuromelanin sensitive, and QSM . Another recent study suggested that the in vivo assessment of neuromelanin with magnetization transfer contrast, particularly in the pSN pars compacta, might be a promising biomarker of the disease . Similar to the ventral SN, PD pathology studies have also shown the pSN to be involved early and to a greater extent when compared with the aSN .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of PD and other neurodegenerative diseases, previous NM imaging has consistently reported a reduction of T1 hyperintensity in the SN and LC, and a link between symptom severity and quantitative measures of neuromelanin loss . Robust normalization and quantification procedures were developed for scanner‐ and protocol‐independent data analysis as a prerequisite for multicenter trials and clinical applications . One potential limitation of these studies is the lack of detailed understanding of the physiological variation of SN pigmentation in vivo across the life span.…”
mentioning
confidence: 99%